2022
DOI: 10.1016/j.fertnstert.2021.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Sperm quality and absence of SARS-CoV-2 RNA in semen after COVID-19 infection: a prospective, observational study and validation of the SpermCOVID test

Abstract: Objective To study the contagiousness of sperm and its influence on fertility after recovery from COVID-19 infection. Design Prospective cohort study. Setting University medical center. Patient(s) One hundred twenty Belgian men who had recovered from proven COVID-19 infection. Intervention(s) No intervention was performed. Main outcome measure(s) Sermm quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(129 citation statements)
references
References 26 publications
8
96
1
5
Order By: Relevance
“…However, we did not evidence a strong correlation between fever and the development of testicular pathogenesis (Spearman’s = -0.195; p= 0.57). Recent data indicate that fever is not correlated with the sperm quality alteration after SARS-CoV-2 infection(16). The most prevalent comorbidities were systemic arterial hypertension (nine cases), diabetes mellitus (six cases), and obesity (six cases).…”
Section: Resultsmentioning
confidence: 99%
“…However, we did not evidence a strong correlation between fever and the development of testicular pathogenesis (Spearman’s = -0.195; p= 0.57). Recent data indicate that fever is not correlated with the sperm quality alteration after SARS-CoV-2 infection(16). The most prevalent comorbidities were systemic arterial hypertension (nine cases), diabetes mellitus (six cases), and obesity (six cases).…”
Section: Resultsmentioning
confidence: 99%
“…Mean progressive sperm motility was reduced in 60%, 37% and 28% of men in the short, intermediate and long follow-up time groups, respectively, whereas mean sperm count was reduced in 37%, 29% and 6% of patients in the three groups, respectively 87 . The authors concluded that the estimated recovery time of sperm quality after COVID-19 infection is 3 months, but further follow-up studies are needed to determine whether a minority of men might suffer from permanent testicular damage 87 . The severity of COVID-19 infection (for example, the need to be hospitalized) and the presence of fever did not correlate with sperm characteristics in this study 87 .…”
Section: Sars-cov-2 and Male Reproductive Healthmentioning
confidence: 88%
“…In a prospective, observational study, sperm quality after recovery from COVID-19 was assessed using the WHO criteria. Sperm parameters were evaluated at three different time points after the infection: short (0–31 days, n = 35); intermediate (32–62 days, n = 51); and long (≥63 days, n = 34) 87 . Mean progressive sperm motility was reduced in 60%, 37% and 28% of men in the short, intermediate and long follow-up time groups, respectively, whereas mean sperm count was reduced in 37%, 29% and 6% of patients in the three groups, respectively 87 .…”
Section: Sars-cov-2 and Male Reproductive Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are corroborated by other studies. Donders et al found sperm quality to be sub-optimal post COVID-19 disease with an estimated recovery time of 3 months (21). In addition, we found significant hyposomia (TDI <31) in those infected in the previous 6 months.…”
Section: Discussionmentioning
confidence: 99%